2012
DOI: 10.1155/2012/861794
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Heterotrophic Ossification with Cryopreserved Poly(ethylene glycol-) Microencapsulated BMP2-Expressing MSCs

Abstract: Autologous bone grafting is the most effective treatment for long-bone nonunions, but it poses considerable risks to donors, necessitating the development of alternative therapeutics. Poly(ethylene glycol) (PEG) microencapsulation and BMP2 transgene delivery are being developed together to induce rapid bone formation. However, methods to make these treatments available for clinical applications are presently lacking. In this study we used mesenchymal stem cells (MSCs) due to their ease of harvest, replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
1
19
0
1
Order By: Relevance
“…While longer time points are critical to the ultimate application of cell transplantation, this level of initial viability is consistent with that of similar eosin photoinitiated PEGDA encapsulation systems with high long term cell viability. 9,23,24 …”
Section: Resultsmentioning
confidence: 99%
“…While longer time points are critical to the ultimate application of cell transplantation, this level of initial viability is consistent with that of similar eosin photoinitiated PEGDA encapsulation systems with high long term cell viability. 9,23,24 …”
Section: Resultsmentioning
confidence: 99%
“…[12] However, microencapsulation of porcine and ovine mesenchymal stromal cells in polyethylene glycol (PEG) hydrogel microcapsules does not affect their survival post cryopreservation also by slow freezing. [13] Moreover, it has been reported that the DMSO concentration could be reduced to 1.5 M for vitrification in QMC (~2.5 μl sample volume) if mouse mesenchymal stem cells were microencapsulated in alginate hydrogel, which is partially attributed to the preferential vitrification of water in alginate hydrogel microcapsule compared to the water in the bulk solution outside the microcapsule during cooling. [8d] However, such vitrification study has not been performed for the more stress-sensitive embryonic stem cells (ESCs) and adult human stem cells, particularly in a large sample volume for the practical application to bank stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers led by Steven Stice (University of Georgia, Athens, Georgia) previously demonstrated how BMP‐2‐expressing MSCs encapsulated in polyethylene glycol (PEG) microspheres induced the creation of ectopic bone and regenerated critically sized bone defects in rats . To improve the clinical potential of this strategy and move toward the development of an injectable biologic therapy for large bone defect healing in humans, Andrews et al next evaluated bone regeneration using a chondroitin sulfate glycosaminoglycan scaffold for the delivery vehicle for recombinant human (rh) BMP‐2 and BMP‐2 overexpressing MSCs.…”
Section: Related Articlesmentioning
confidence: 99%